2021
DOI: 10.1097/mpg.0000000000003135
|View full text |Cite
|
Sign up to set email alerts
|

The Farnesoid X Receptor Agonist Tropifexor Prevents Liver Damage in Parenteral Nutrition‐fed Neonatal Piglets

Abstract: Objectives: Intestinal failure-associated liver disease (IFALD) is a lifethreatening complication for patients with intestinal failure who receive long-term parenteral nutrition (PN). We evaluated the effects of the farnesoid X receptor agonist tropifexor on a neonatal piglet model of IFALD fed with PN. Methods: The piglets received PN and tropifexor for 14 days, then levels of liver enzymes, bile acid metabolism, inflammation, and intestinal barrier markers were assessed using quantitative real-time PCR. Fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…**P < 0.01. CA, cholic acid; CDCA, chenodeoxycholic acid; HCA, hyocholic acid; HDCA, hyodeoxycholic acid; LCA, lithocholic acid; ns, not significant; UDCA, ursodeoxycholic acid Consistently, we found LP administration increased the expression levels of intestinal FGF19 and hepatic SHP to reduce the protein expression of CYP7A1, resulting in the reduction of BAs synthesis.Previous study found the FXR agonist tropifexor increased the expression levels of antioxidative genes (GCLM and SOD1) to reduce oxidative stress in the liver of PN-fed piglets 14. Consistently, LP administration increased the expression of GCLM and SOD1, suggesting that LP may reduce oxidative stress in the liver of F I G U R E 4 Lactobacillus plantarum CGMCC 1258 (LP) alters the metabolism of bile acids (BAs) in piglets.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…**P < 0.01. CA, cholic acid; CDCA, chenodeoxycholic acid; HCA, hyocholic acid; HDCA, hyodeoxycholic acid; LCA, lithocholic acid; ns, not significant; UDCA, ursodeoxycholic acid Consistently, we found LP administration increased the expression levels of intestinal FGF19 and hepatic SHP to reduce the protein expression of CYP7A1, resulting in the reduction of BAs synthesis.Previous study found the FXR agonist tropifexor increased the expression levels of antioxidative genes (GCLM and SOD1) to reduce oxidative stress in the liver of PN-fed piglets 14. Consistently, LP administration increased the expression of GCLM and SOD1, suggesting that LP may reduce oxidative stress in the liver of F I G U R E 4 Lactobacillus plantarum CGMCC 1258 (LP) alters the metabolism of bile acids (BAs) in piglets.…”
mentioning
confidence: 78%
“…33 Previous studies found the FXR agonist tropifexor alleviated intestinal injury. 14,18 Furthermore, LP administration facilitated the gut health of suckling piglets by improving the intestinal morphology and intestinal barrier function and microflora. 34 Consistently, we found LP administration alleviated intestinal injury, ameliorated intestinal inflammation, and promoted the expression of genes related to the intestinal barrier in the PN piglets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations